The influence of green lifestyle, green awareness, and eco-labels on the interest in purchasing environmentally friendly products among FEBI UINSU students - Intan Vilja Aura Fazia; Fauzi Arif Lubis; Nur Ahmadi Bi Rahmani (Indonesia Auditing Research Journal, 2026)
Focusing on the consumption behavior of FEBI UINSU students, this associative quantitative research examines the relationship between green lifestyle, green awareness, and eco-labeling on the purchase intention of environmentally friendly products. Involving 100 students selected through purposive sampling, a questionnaire instrument was used as the primary data collection medium, which was then analyzed using the SEM-PLS algorithm via SmartPLS 4.0. Field findings show that a green lifestyle is not yet a strong predictor in significantly predicting purchase intention, even though the relationship is positive. In contrast, indicators of green awareness and eco-friendly labels show a substantial positive impact. These findings underscore the importance of environmental education and the effectiveness of product labels in stimulating sustainable purchasing decisions among academics